Dyeing and characterization of regenerated cellulose nanofibers with vat dyes. (15th October 2017) - Khatri, Muzamil; Ahmed, Farooq; Shaikh, Irfan; Phan, Duy-Nam; Khan, Qamar; Khatri, Zeeshan; Lee, Hoik; Kim, Ick Soo
Graphical abstract: Highlights: Regenerated cellulose nanofibers were fabricated by electrospinning followed by deacetylation. Regenerated cellulose nanofibers were dyed with vat dyes for the very first time. Smooth morphology was observed before and after vat dyeing of regenerated cellulose nanofibers. Dyed regenerated cellulose nanofiber showed increased crystallinity. Very good color fastness properties achieved. Abstract: Recent advancement in dyeing of nanofibers has been accelerated to improve their aesthetic properties, however, achieving good color fastness remains a challenge. Therefore, we attempt to improve the color fastness properties nanofibers. Vat dyes are known for better color fastness and their application on nanofibers has not been investigated to date. Herein, we report dyeing of regenerated cellulose nanofibers (RCNF) that were produced from precursor of cellulose acetate (CA) followed by deacetylation process. The resultant RCNF was dyed with two different vat dyes and the color attributes were examined under spectrophotometer which showed outstanding color build-up. Morphological of CA before and after deacetylation and before and after vat dyeing was investigated under TEM, FE-SEM and SEM respectively. The vat dyed RCNF were further characterized by FTIR and WAXD. Excellent color fastness results demonstrate that vat dyed RCNF can potentially be considered for advanced apparel applications.